Libraries and Research: A Study of the Availability of Library Collections - Khoirul Maslahah; Nushrotul Hasanah Rahmawati (Edumaspul: Jurnal Pendidikan, 2025)
Abstract English version, written using Times New Roman-11, italic. The abstract contains This study aims to determine the role of libraries in the research process in 2022 at UIN Raden Mas Said Surakarta and UNS. This can be seen from the availability of collections from all references used by researchers for research and other supporting factors. This study uses a mixed quantitative-qualitative method. The quantitative data collection technique uses primary data which is the result of research by lecturers and certain functional positions with sampling based on the Isaac and Michael table with an error rate of 10%, namely 27 at UIN Raden Mas Said Surakarta and 217 for UNS research. While for qualitative research, observation, interviews and documentation are carried out. The study found that the library at UIN Surakarta has not yet functioned as a Research Library. This is indicated by the availability of book collections supporting research in 2022, which was only 27%, a relatively low percentage. Additionally, in terms of library support for research, many services have not yet been provided. Meanwhile, the UNS Library was found to have played a moderate role (44%) in supporting lecturers' research and specific functional positions in 2022. This role was supported by the availability of facilities, infrastructure, various training programs, and supporting data provided by the library. Library support for lecturers’ and specific functional positions’ research at UIN Raden Mas Said remains low, both in terms of collections and services. Meanwhile, the support provided by the UNS Library for research in 2022 is categorized as moderate, both in terms of services and collections